Legal Standing and Qualifications of the Petitioner in the Judicial Review from the Perspective of Fiqh Siyasah - Waryanto Waryanto; Siti Ngainnur Rohmah (STAATSRECHT: Indonesian Constitutional Law Journal, 2022)
The delay in development is the same as the delay in efforts to realize prosperity for the people of Indonesia. Indonesia Corruption Watch (ICW) noted that state financial losses arising from corruption cases throughout 2021 reached Rp 62.9 trillion. This amount exceeded the previous year with a total loss of Rp 56.7 trillion. Pungki Harmoko, revealed in his application for judicial review in 2015, the facts of losses to the state and society due to corruption, that: (1) Corruption is increasingly prevalent; (2) There is a desire from the people represented by Nahdlatul Ulama and Muhammadiyah so that corruptors get the death penalty. However, the Constitutional Court decided that the Petitioner did not have the legal standing to file the a quo petition. The researcher tries to explore the legal standing and qualifications of the applicant in the Judicial Review and is reviewed in the fiqh siyasah. After researching that the legal standing and qualifications of the applicant in the Judicial Review of the decision of the Constitutional Court Number 112/PUU-XIII/2015, are in accordance with the Constitutional Court Law. Thus Pungki Harmoko does not have legal standing as an applicant. Likewise with the Legal Standing and Qualifications of the Petitioners in the Judicial Review from the Fiqh Siyasah Perspective. In the review of the decision of the Constitutional Court Number 112/PUU-XIII/2015, it has also been in accordance with what is argued in the Constitutional Court Law.Kata Kunci: Judicial Review,Legal Standing, Kualifikasi Pemohon AbstrakTerhambatnya pembangunan sama dengan terhambatnya usaha mewujudkan kesejahteraan bagi rakyat Indonesia. Indonesia Corruption Watch (ICW) mencatat kerugian keuangan negara yang timbul akibat kasus korupsi sepanjang 2021 mencapai Rp 62,9 triliun. Jumlah tersebut melampaui tahun sebelumnya dengan jumlah kerugian sebesar Rp 56,7 triliun. Pungki Harmoko, mengungkapkan dalam permohonan uji materinya pada tahun 2015, fakta-fakta kerugian negara dan masyarakat akibat korupsi, bahwa: (1) Korupsi yang semakin menggurita; (2) Adanya keinginan dari rakyat yang terwakili oleh Nahdlatul Ulama dan Muhammadiyah agar para koruptor mendapat hukuman mati. Namun Mahkamah Konstitusi memutuskan Pemohon tidak memiliki kedudukan hukum (legal standing) untuk mengajukan permohonan a quo. Peneliti mencoba menggali legal standing dan kualifikasi pemohon dalam Judicial Review dan ditinjau dalam fiqh siyasah. Setelah diteliti bahwa Legal standing dan kualifikasi pemohon dalam Judicial Review putusan Mahkamah Konstitusi Nomor 112/PUU-XIII/2015, telah sesuai dengan UU MK. Dengan demikian Pungki Harmoko tidak memiliki legal standing sebagai pemohon. Begitu juga dengan Legal Standing Dan Kualifikasi Pemohon Dalam Judicial Review Perspektif Fiqh Siyasah. Dalam Review putusan Mahkamah Konstitusi Nomor 112/PUU-XIII/2015, juga telah sesuai dengan yang didalilkan dalam UU MK.Keywords: Judicial Review, Legal Standing, Applicant Qualifications